Reactive Oxygen Species Induced Upregulation of TRPV1 in Dorsal Root Ganglia Results in Low Back Pain in Rats - Chen X; Chen Z; Ma G; Sha J; Zhao S; Liu Z; Chen N; Yang H (Dove Medical Press, 2024)
Xinyong Chen,1,2,* Zhe Chen,3,* Gongchang Ma,2 Jianjun Sha,2 Shan Zhao,2 Zuoqing Liu,2 Nong Chen,2 Huilin Yang1 1Department of Orthopedics, The First Affiliated Hospital of Soochow University, Suzhou, 215000, People's Republic of China; 2Department of Orthopedics, Qingpu Branch of Zhongshan Hospital Affiliated to Fudan University, Shanghai, 200025, People's Republic of China; 3Department of Orthopedics, Ruijin Hospital, Shanghai Jiaotong University School of Medicine, Shanghai, 200025, People's Republic of China*These authors contributed equally to this workCorrespondence: Nong Chen, Department of Orthopedics, Qingpu Branch of Zhongshan Hospital Affiliated to Fudan University, Shanghai, 200025, People's Republic of China, Email chennong1975@126.com Huilin Yang, Department of Orthopedics, The First Affiliated Hospital of Soochow University, Suzhou, 215000, People's Republic of China, Email orthdoctor@126.comBackground: Dorsal root ganglia (DRGs) contain sensory neurons that innervate intervertebral discs (IVDs) and may play a critical role in mediating low-back pain (LBP), but the potential pathophysiological mechanism needs to be clarified.Methods: A discogenic LBP model in rats was established by penetration of a lumbar IVD. The severity of LBP was evaluated through behavioral analysis, and the gene and protein expression levels of pro-algesic peptide substance P (SP) and calcitonin gene-related peptide (CGRP) in DRGs were quantified. The level of reactive oxygen species (ROS) in bilateral lumbar DRGs was also quantified using dihydroethidium staining. Subsequently, hydrogen peroxide solution or N-acetyl-L-cysteine was injected into DRGs to evaluate the change in LBP, and gene and protein expression levels of transient receptor potential vanilloid-1 (TRPV1) in DRGs were analyzed. Finally, an inhibitor or activator of TRPV1 was injected into DRGs to observe the change in LBP.Results: The rats had remarkable LBP after disc puncture, manifesting as mechanical and cold allodynia and increased expression of the pro-algesic peptides SP and CGRP in DRGs. Furthermore, there was significant overexpression of ROS in bilateral lumbar DRGs, while manipulation of the level of ROS in DRGs attenuated or aggravated LBP in rats. In addition, excessive ROS in DRGs stimulated upregulation of TRPV1 in DRGs. Finally, activation or inhibition of TRPV1 in DRGs resulted in a significant increase or decrease of discogenic LBP, respectively, suggesting that ROS-induced TRPV1 has a strong correlation with discogenic LBP.Conclusion: Increased ROS in DRGs play a primary pathological role in puncture-induced discogenic LBP, and excessive ROS-induced upregulation of TRPV1 in DRGs may be the underlying pathophysiological mechanism to cause nerve sensitization and discogenic LBP. Therapeutic targeting of ROS or TRPV1 in DRGs may provide a promising method for the treatment of discogenic LBP.Keywords: lower back pain, reactive oxygen species, dorsal root ganglion, transient receptor potential vanilloid-1, substance p, calcitonin gene related peptide, intervertebral disc